Out-of-field dose assessment for pencil beam scanning proton radiotherapy versus photon radiotherapy for breast cancer in pregnant women - Menke Weessies; Murillo Bellezzo; Britt J.P. Hupkens; Frank Verhaegen; Gloria Vilches-Freixas (Physics and Imaging in Radiation Oncology)
Background and purpose: Cancer affects 1 in 1000–2000 pregnancies annually worldwide, creating challenges in balancing cancer treatment and fetal safety. This study compares out-of-field radiation doses between two treatment modalities: 6MV external photon radiotherapy (XRT) and pencil beam scanning proton-therapy (PBS-PRT) for breast cancer, including imaging, to evaluate PBS-PRT as a potential new treatment option. Materials and methods: For breast cancer involving lymph node levels 1–4 and the intramammary lymph nodes, treatment plans were created for XRT (with Flattening Filter (FF) and FF-Free (FFF)) and PBS-PRT, prescribing 15 × 2.67 Gy(RBE). Measurements were conducted using an adapted anthropomorphic phantom representing 20- and 30-week pregnancy. Bubble detectors placed in the phantom’s abdomen assessed neutron dose from PBS-PRT, while a Farmer ion chamber was used for imaging and XRT dose. Results: At 20 weeks, PBS-PRT including imaging delivered 22.4 mSv, reducing dose 3.4-fold versus 6FF XRT and 2.5-fold versus 6FFF XRT. At 30 weeks, the PBS-PRT dose was 25.4 mSv, resulting in 7.6-fold and 6.3-fold reductions compared to 6FF and 6FFF XRT, respectively. Conclusions: This study presents the first one-by-one comparison between PBS-PRT and different XRT modalities for pregnant breast cancer patients with an adapted anthropomorphic phantom. PBS-PRT measurements showed that the total equivalent dose was below the 100 mSv threshold outlined in AAPM Task Group Report No. 36 for a 30-week pregnancy, even under a worst-case scenario, maintaining treatment goals. These findings support the adoption of PBS-PRT as the preferred approach for treating pregnant breast cancer patients, should radiotherapy be required.